CMFrame : framework para o gerenciamento de históricos de contextos dinâmicos e hierárquicos - Vielitz, Felipe Lauermann (Universidade do Vale do Rio dos Sinos, 2018)
With the increasing availability of devices capable of capturing information about their surroundings and the expansion of connectivity in mobile devices, Internet of Things solutions have come to integrate more and more aspects of society. In order for IoT solutions to emerge successfully in the market, it becomes necessary to employ more than the traditional mobile computing from smartphones and portables, instead making use of day-to-day objects in an interconnected way and adding intelligence to environments. The search for environments capable of proactivity will empower the experiences of the population both in matters related to work as those of leisure, providing objects with intelligent characteristics that adapt to the current situation without the need for human intervention With the intention of providing this adaptation or response to their surroundings, it becomes necessary that the environments be aware of their circumstance at any given moment, for this purpose, the development of CMFrame is proposed, a framework for managing context information captured in a physical environment, in the form of a history, through the use of hierarchical and dynamic entities. From this concept, entities can modify their hierarchical organization to redefine to whom a certain context is linked at that moment. The contexts attached to each entity are also dynamic and can store different amounts of values at any given time, varying indefinitely as the need arises. The framework was evaluated through the development of two applications, in which the characteristics offered by CMFrame regarding the use of their hierarchical and dynamic entities were investigated. The results of this evaluation show that the framework serves the needs as a context history manager, for situations that use physical environments with intelligent elements and applications that manage the environment by acting on them.
Keywords: Framework; Contexto; Históricos de contextos; Framework; Context; Contexts histories; ACCNPQ::Ciências Exatas e da Terra::Ciência da Computação